Convolution and Coefficient Estimates for (p, q)-Convex Harmonic Functions Associated with Subordination. (15th September 2022) - Bayram, Hasan; Yalçın, Sibel
Abstract : We preface and examine classes of (p, q)-convex harmonic locally univalent functions associated with subordination. We acquired a coefficient characterization of (p, q)-convex harmonic univalent functions. We give necessary and sufficient convolution terms for the functions we will introduce.